Measuring the Size and Growth of Cities Using Nighttime Light (2020)
This paper uses nighttime luminosity to estimate a globally comparable measure of the size of metropolitan areas around the world for the years 2000 and 2010. We apply recently-proposed methodologies that correct the known problems of available nighttime luminosity data including blurring, instability of lit pixels overtime and the reduced comparability of night light images across satellites and across time. We then develop a protocol that isolates stable nighttime lit pixels that constitute urban footprint. When analyzed together with existing geo-referenced population datasets, our measure of the size of metropolitan areas can be used to compute urbanization rates, urban densities, and study the size distribution of cities. We show these applications and discuss how they compare with other available figures. © 2020 Elsevier Inc.